2011
DOI: 10.3109/10242422.2011.591927
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of 5α-hydroxycaryophylla-4(12),8(13)-diene withCunninghamella elegansandRhizopus stolonifer

Abstract: Biotransformation of 5 α -hydroxycaryophylla-4(12),8(13)-diene ( 1 ) was studied with Cunninghamella elegans and Rhizopus stolonifer . Incubation of 1 with C. elegans gave regioselective oxidative addition (hydration) and isomerization at the C-4(12) exocyclic double bond and hydroxylation at C-3 and C-15, and thus provided two polar metabolites, (3 Z ),8(14)-caryophylladiene-5 α ,(11 R )-15-diol ( 2 ) and 3 β ,4 β ,5 α -trihydroxycaryophylla-8(13)-ene ( 3 ). Incubation of 1 with R. stolonifer gave a transannu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…218 Biotransformations of 5a-hydroxycaryophyll-4(12),8(13)-diene with the fungi Cunninghamella elegans and Rhizopus stolonifer have been reported. 219 The rst total synthesis of rumphellaone A has been accomplished. 220 It has been shown that b-caryophyllene and caryophyllene oxide act as phytogrowth and photosynthesis inhibitors.…”
Section: Cadinane Copaane Oplopane and Cubebanementioning
confidence: 99%
“…218 Biotransformations of 5a-hydroxycaryophyll-4(12),8(13)-diene with the fungi Cunninghamella elegans and Rhizopus stolonifer have been reported. 219 The rst total synthesis of rumphellaone A has been accomplished. 220 It has been shown that b-caryophyllene and caryophyllene oxide act as phytogrowth and photosynthesis inhibitors.…”
Section: Cadinane Copaane Oplopane and Cubebanementioning
confidence: 99%
“…In continuation of our biotransformational studies on bioactive compounds [14-20], structural transformation of (−)-ambrox ( 1 ) with Macrophomina phaseolina and Peganum harmala was studied which afforded nine oxidative metabolites 2 10 . Compounds 2 , 3 , 5 , 6 10 were previously reported as metabolites of compound 1 [18,19,21].…”
Section: Introductionmentioning
confidence: 99%